2017
DOI: 10.1080/14786419.2017.1371166
|View full text |Cite
|
Sign up to set email alerts
|

Polyketides with different post-modifications from desert endophytic fungus Paraphoma sp.

Abstract: Three new polyketides 4,6,8-trihydroxy-5-methyl-3,4-dihydronaphthalen-1(2H)-one (1), 5,7-dihydroxy-3-(1-hydroxyethyl)-3,4-dimethylisobenzofuran-1(3H)-one (2) and 1-(4-hydroxy-6-methoxy-1,7-dimethyl-3-oxo-1,3-dihydroisobenzofuran-1-yl) ethyl acetate (3) together with seven known analogues (4-10) were isolated from desert endophytic fungus Paraphoma sp. The structures of these compounds were elucidated by analysis of NMR data. The absolute configuration of (1-3) was established on the basis of CD experiments. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…According to the ring size, this member of secondary metabolites are further divided into 8-membered, 10-membered, 12-membered, and 14-membered ring subgroups, though the 10-membered ring analogs rarely occurred in nature. This group of secondary metabolites exhibited versatile biological effects, including antitumor, antibacterial, and antimalarial activities, and recently the 14-membered ring RALs with a cis -enone group in the macrocyclic ring have been reported to display irreversible but selective inhibition against different protein kinases due to the hetero-Michael reaction with a conserved cysteine in the ATP binding pocket. In 1999, Pearl and co-workers obtained the cocrystal structure of the RAL radicicol with Hsp90, implying that the carbonyl group in the macrocycle and 9/11-OH on the aromatic ring were the potentially biological functionalities, mimicking the adenosines’s binding interactions with different amino acids groups in Hsp90 by hydrogen-bonds . Investigation of RALs biogenetic pathway revealed that this class of mycotoxins were originated from two polyketide synthases (PKSs) including one highly reducing one and another nonreducing one, which formed the corresponding macrocyclic lactone ring and resorcylate core, respectively. ,,, Our lab recently initiated chemical investigation of plant endophytic fungi isolated from desert and grassland plants inhabiting in Northwest of China, including Ning-xia, Qing-hai, Shaan-xi, Xin-jiang, Inner Mongolia Provinces, and a series of secondary metabolites with diverse structural features and a wide range of biological effects were purified. During our ongoing to obtain bioactive natural products from this member of special fungi, five new RAL analogs hispidulactones A–E ( 1 , 4 , 5 , 8 , and 9 ), a new natural product ( 2 ) and four known analogs ( 3 , 6 , 7 , and 10 ) with different ring systems were purified from the plant endophytic fungus Chaetosphaeronema hispidulur (Number: TS-8-1) collected from the desert plant Bassia dasyphylla in Teng–Ge–Li desert, Ning-xia Province of West China (Figure ). The structural elucidation, biological evaluation, and possible biosynthetic pathway of these compounds were presented in this report.…”
Section: Introductionmentioning
confidence: 99%
“…According to the ring size, this member of secondary metabolites are further divided into 8-membered, 10-membered, 12-membered, and 14-membered ring subgroups, though the 10-membered ring analogs rarely occurred in nature. This group of secondary metabolites exhibited versatile biological effects, including antitumor, antibacterial, and antimalarial activities, and recently the 14-membered ring RALs with a cis -enone group in the macrocyclic ring have been reported to display irreversible but selective inhibition against different protein kinases due to the hetero-Michael reaction with a conserved cysteine in the ATP binding pocket. In 1999, Pearl and co-workers obtained the cocrystal structure of the RAL radicicol with Hsp90, implying that the carbonyl group in the macrocycle and 9/11-OH on the aromatic ring were the potentially biological functionalities, mimicking the adenosines’s binding interactions with different amino acids groups in Hsp90 by hydrogen-bonds . Investigation of RALs biogenetic pathway revealed that this class of mycotoxins were originated from two polyketide synthases (PKSs) including one highly reducing one and another nonreducing one, which formed the corresponding macrocyclic lactone ring and resorcylate core, respectively. ,,, Our lab recently initiated chemical investigation of plant endophytic fungi isolated from desert and grassland plants inhabiting in Northwest of China, including Ning-xia, Qing-hai, Shaan-xi, Xin-jiang, Inner Mongolia Provinces, and a series of secondary metabolites with diverse structural features and a wide range of biological effects were purified. During our ongoing to obtain bioactive natural products from this member of special fungi, five new RAL analogs hispidulactones A–E ( 1 , 4 , 5 , 8 , and 9 ), a new natural product ( 2 ) and four known analogs ( 3 , 6 , 7 , and 10 ) with different ring systems were purified from the plant endophytic fungus Chaetosphaeronema hispidulur (Number: TS-8-1) collected from the desert plant Bassia dasyphylla in Teng–Ge–Li desert, Ning-xia Province of West China (Figure ). The structural elucidation, biological evaluation, and possible biosynthetic pathway of these compounds were presented in this report.…”
Section: Introductionmentioning
confidence: 99%
“…CR1546 C . Compound 6 was also reported from red oak pathogenic fungus Tubakia dryina , fresh‐water‐derived unidentified fungus YMF1.01029, marine‐associated fungus Daldinia eschscholzii , endophytic Microsphaeropsis arundinis , and Paraphoma sp . Compound 6 was non‐specific phytotoxin that caused large necrosis when placed on leaves of red oak .…”
Section: Resultsmentioning
confidence: 92%
“…MSX63693 had 3R,4S absolute configuration as confirmed via ECD calculations, using TDDFT (time-dependent density functional theory). It showed weak activity (IC 50 > 25 µM) versus MDA-MB-435, MDA-MB-231 (human breast cancer cell line), and OVCAR3 (human ovarian cancer cell line) in the MTT assay [87]. The purification of Paraphoma sp.…”
Section: Cytotoxic Activitymentioning
confidence: 98%